The Mediating and Moderating Effect on the Relationship between Performance Appraisal, Leader-Member Exchange and Job Performance in Public Higher Educational Institutions in Pakistan - Muhammad, Aamir (2023)
The current study was aimed to investigate the impact of performance appraisal on job performance of employees working in public sector educational institutions of Pakistan with a mediation moderation mechanism. The previous literature highlighted the gaps relevant to performance appraisal and its impact on job performance of employees in different sectors. The current study incorporated organizational commitment as a moderator and LMX as a mediator to further strengthen the positive relationship between these two variables. Structural equation modeling (SEM) with maximum likelihood estimation was applied with a sample of 332 employees working in 12 public sector higher educational institutions located in Islamabad, Pakistan. The results further explored the role of performance appraisal and its direct and positive impact on job performance of employees. In addition, LMX have a direct and positive impact on job performance, while it also mediates the positive relationship of performance appraisal and job performance of employees in these selected public sector educational organizations. The study concludes that, in light of the preceding analysis and discussion regarding the influence of performance appraisals on employee job performance in educational institutions in Pakistan, organizations must pay adequate attention to their human resources in order to improve organizational performance. The research emphasizes the importance of recognition and feedback in an employee's performance and how they impact employee job performance in a public sector university. Surprisingly, however, training, development, and promotion had little influence on staff productivity and performance. It is therefore critical that staff performance may be increased by timely feedback and appreciation via tangible benefits. Based on the foregoing results, it is suggested that, in order to boost employee performance, training and promotion should focus on strengthening employees' commitment and be performance-based. Performance appraisal has a significant and an important role in improving employee performance within an educational organization. As a result, university administration should develop and implement the finest performance assessment techniques to increase employee competency while also meeting organizational goals. Furthermore, university administration should ensure that job descriptions for each staff member are clear, specific, and well defined in order to prevent employee confusion and dissatisfaction in cases where they do not know what is required of them, which may result in failure to meet their set targets. Future research should look into the performance appraisal system and its secondary outcomes, such as corporate innovation, financial performance, quality performance, and so on, while taking the mediation role of internal communication, employee motivation, and employee training and development into account.